A Kohutian approach to indecisiveness - Santos, Paulo Jorge (2017)
Career indecision is a classic topic in vocational psychology and presently it is regarded as a multidimensional construct. Career undecided individuals have been classified into two main categories. The first corresponds to a normal phase, in development terms, of career exploration of alternatives that precedes investment in a specific career option. The second, normally called indecisiveness, is of more structural nature. For indecisive individuals, and not simply undecided, the decision making process, including career choice, tends to be a difficulty task. The identification of the determinants of indecisiveness has important implications for career counseling. Based on the self-psychology of Heinz Kohut, the primary purpose of this study was to analyze the role of goal instability and self-esteem, two markers of the self's maturity according to this psychological framework of psychoanalytical orientation, in the prediction of indecisiveness. A regression analysis was applied to a Portuguese high-school sample of 314 secondary school students. Overall, the regression equation accounted for 35% of indecisiveness scores. Implications for career theory and counseling are discussed.